ESTIMATING AND ANALYZING THE STABILITY OF BRAZILIAN GNSS STATIONS FOR TECTONIC STUDIES - Almeida, Yellinson de Moura; Marotta, Giuliano Sant’Anna; Monico, João Francisco Galera; Brassarote, Gabriela de Oliveira Nascimento [UNESP]; França, George Sand Leão A. (Sociedade Brasileira de Geofisica, 2024)
The detailed study of stresses and strains is fundamental for geophysical and geodetic studies, enabling the development of plate motion models, geodynamic processes and several proposals. GNSS positioning has been used to estimate these stresses and strains. However, for the accuracy required, it is necessary a rigorous assessment of the behavior of GNSS stations and their position time series. This paper aims to analyze the influence of the different types of geodetic monuments present in the Brazilian GNSS Continuous Monitoring Network by estimating and characterizing noise in the time series and investigating variables that can affect the stability of the stations to establish criteria for using this data in tectonic and geodynamic studies. The evaluation of 119 GNSS stations throughout Brazil indicates the significant presence of random walk noise in some of these stations, detected by analyzing the magnitude of the noise and the spectral index. It was found that the stations with unstable monuments have been observed for at least eight years and are mostly in coastal areas or under the influence of large watercourses.
Keywords: Geodetic monuments; Geodynamic processes; Noise characterization; Time series analysis